Cartas marcadas: an??lise de preconceito (s) em cartas de alunos de uma escola do sistema prisional do estado de S??o Paulo - Marsiglia, Denys Munhoz (2017)
The prison system in Brazil faces a serious crisis, translating into a degrading ambience, structures that confine individuals to the light of their own barbarity, little working condition with low technical and moral capacity. In this scenario, a school is set up. To think of jail is to rethink the body of many people in degrading conditions of survival. The story portrayed the prison used as a place of punishment, torture and death for any individual who deviated from socially constructed standards at different historical moments. Today, the reality portrayed is the domination of criminals in closed structures, even over the eyes of penitentiary agents and society and without any goal of regeneration, because their practices, besides imprisoning the body, damage the soul by the minimum conditions of survival. But the prison does not establish a total social dissociation, because in its buildings circulates family, agents, lawyers and all those involved in this complex system. This coexistence is difficult because it is permeated by several problems that reflect life in this social locus. In this sense, the school appears in this space as an alternative in the process of resocialization of these inmates. Even offering remission of the sentence, the adhesions to the study of the prison population are very low compared to the work that, besides the remission, also offered some remuneration. The individuals who are there, almost in their entirety, are black, from the most impoverished layers of society, with some kind of vice and family disruption. Based on these contexts, this research seeks to study the social marks and portraits of these individuals discriminated and marginalized socially. Prisons do not play their role as a social regenerator and these obstacles create the need to study the motives behind the search for deviant and aggressive patterns in society. The object of study is the letters of students from a school in the prison system of S??o Paulo. The hypothesis pointed out is that the stigma of prejudice will be present in the life trajectory of students detained in a prison in the state of S??o Paulo. Our objective is to identify the processes of subjectivation grooved and crossed by discrimination and prejudice in the life trajectory of these subjects. The method used in this study is the qualitative, through field research in letters. Twenty letters were collected in 2015 from students detained in a penitentiary of Franco da Rocha in the science classes of a linked school and inserted in the Education Program in the Prisons of the Government of the State of S??o Paulo. Among them, we chose 9 letters for analysis. All of them demonstrate that these subjects are / have been victims of discriminatory actions in social relations, as well as fragile and unstructured family relationships, and are still marked by prejudice in their life trajectories. The school, in this context, seems to exercise a power of liberation through educational practice and conquest of citizenship and the remission of their sentences in prison.